Impact of Aphasia on Consciousness Assessment: A Cross-Sectional Study. (January 2015) - Schnakers, Caroline; Bessou, Helene; Rubi-Fessen, Ilona; Hartmann, Alexander; Fink, Gereon R.; Meister, Ingo; Giacino, Joseph T.; Laureys, Steven; Majerus, Steve
Background . Previous findings suggest that language disorders may occur in severely brain-injured patients and could interfere with behavioral assessments of consciousness. However, no study investigated to what extent language impairment could affect patients' behavioral responses. Objective . To estimate the impact of receptive and/or productive language impairments on consciousness assessment. Methods . Twenty-four acute and subacute stroke patients with different types of aphasia (global, n = 11; Broca, n = 4; Wernicke, n = 3; anomic, n = 4; mixed, n = 2) were recruited in neurology and neurosurgery units as well as in rehabilitation centers. The Coma Recovery Scale–Revised (CRS-R) was administered. Results . We observed that 25% (6 out of 24) of stroke patients with a diagnosis of aphasia and 54% (6 out of 11) of patients with a diagnosis of global aphasia did not reach the maximal CRS-R total score of 23. An underestimation of the consciousness level was observed in 3 patients with global aphasia who could have been misdiagnosed as being in a minimally conscious state, even in the absence of any documented period of coma. More precisely, lower subscores were observed on the communication, motor, oromotor, and arousal subscales. Conclusion . Consciousness assessment may be complicated by the co-occurrence of severe language deficits. This stresses the importance of developing new tools or identifying items in existing scales, which may allow the detection of language impairment in severely brain-injured patients.